2018
DOI: 10.1111/raq.12319
|View full text |Cite
|
Sign up to set email alerts
|

Environmental colour impact on the life of lower aquatic vertebrates: development, growth, physiological and biochemical processes

Abstract: This review discusses environmental colour impact on such vital processes of lower aquatic vertebrates (amphibian and fish), as development, growth, consumption of food and its conversion ratio, secretion of hormones etc. For some species, different zones of the spectrum can act as a stimulator of growth and development processes, while other zones of the spectrum can, on the contrary, inhibit development and growth. This influence occurs at the physiological and biochemical levels. Physiologically, environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 117 publications
1
21
0
Order By: Relevance
“…Interestingly, these results coincide with our findings of antioxidant activity of the mixture of QS/ YS and, hence, this protects gills' tissues from the inflammatory and degenerative influences of free radicals (Dawood et al, 2021;Elbialy et al, 2020;Elkaradawy et al, 2021). lymphocytes production improved the lysozyme activity, which modulated fish's immune status (Choi et al, 2013;Ruchin, 2020).…”
Section: Ta B L Esupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, these results coincide with our findings of antioxidant activity of the mixture of QS/ YS and, hence, this protects gills' tissues from the inflammatory and degenerative influences of free radicals (Dawood et al, 2021;Elbialy et al, 2020;Elkaradawy et al, 2021). lymphocytes production improved the lysozyme activity, which modulated fish's immune status (Choi et al, 2013;Ruchin, 2020).…”
Section: Ta B L Esupporting
confidence: 90%
“…Likewise, Njagi et al (2017) stated that Nile tilapia fed a diet containing 100 mg/ kg YS had the highest lysozyme activity, which was significantly higher than that of the control. The increased lysozyme activity may be attributed to the higher lymphocytes production which modulated fish's immune status (Choi et al, 2013;Ruchin, 2020).…”
Section: Ta B L Ementioning
confidence: 99%
“…Therefore, each treatment was only influenced by a certain color or wavelength of the light. There are not many studies reported of the influence of colored light on the growth of Nile tilapia and fish of different species in general [18], and as far as we know, this is the first study on the fingerling stage of development of tilapia. Even more, all previous studies on light effect use other experimental conditions, which include significant differences in: The lack of biofloc, the type or duration of photoperiod, the temperature, the light intensity, peak wavelengths, light spectrum shapes, etc.…”
Section: Discussionmentioning
confidence: 94%
“…Since its origin, life has adapted over several billion years to the daily and annual fluctuations of factors in the abiotic environment, where the light factor stands out for its versatility (Boeuf & Le Bail 1999;Ruchin, 2020b). It serves not only as a source of energy, but also as a source of information for organisms which stimulates daily and seasonal cycles of behaviour, phenology and physiological changes (Ruchin, 2007a(Ruchin, , 2007bNiven & Laughlin 2008;Villamizar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%